2005
DOI: 10.1109/tcomm.2005.851626
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Capacity Statistics for Short VDSL Loops

Abstract: Abstract-We assess the capacity potential of very short very-high data-rate digital subscriber line loops using full-binder channel measurements collected by France Telecom R&D. Key statistics are provided for both uncoordinated and vectored systems employing coordinated transmitters and coordinated receivers. The vectoring benefit is evaluated under the assumption of transmit precompensation for the elimination of self-far-end crosstalk, and echo cancellation of self-near-end crosstalk. The results provide us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Assume that only user i transmits, there is no interference, and the processor in the ONU only needs to collect the energy received by all receivers. Thus, user i can achieve a data rate of: 7 Maximizing over all users and using definition (15) leads to (22). The second inequality, (23), comes from the observation that β U,2 ≤ β 2 U,max .…”
Section: Umaxmentioning
confidence: 99%
“…Assume that only user i transmits, there is no interference, and the processor in the ONU only needs to collect the energy received by all receivers. Thus, user i can achieve a data rate of: 7 Maximizing over all users and using definition (15) leads to (22). The second inequality, (23), comes from the observation that β U,2 ≤ β 2 U,max .…”
Section: Umaxmentioning
confidence: 99%
“…Note that in [3] it is shown that DSM3 provides significant capacity gains only when almost all pairs in a binder are coordinated.…”
Section: Justification Of the Assumptionsmentioning
confidence: 99%
“…We let SNR i (f ) be as in (15) and let Γ be the Shannon Gap comprising modulation loss, coding gain and noise margin. Let R i be the achievable transmission rate of the i-th user in the system defined in (3). Recall that in such a system the crosstalk is completely removed and therefore…”
Section: B Transmission Loss Of a Single Usermentioning
confidence: 99%
“…Future digital subscriber line (DSL) networks are expected to fulfill demands of very high data rates in a fast growing market. Installing optical fibres in the access networks helps reduce the lengths of used copper segments to carry out much higher throughputs [1]. In such configuration, crosstalk between copper pairs may become orders of magnitude larger than background noise and so is considered as the performance-limiting factor.…”
Section: Introductionmentioning
confidence: 99%